2017
DOI: 10.1016/j.earscirev.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of soil erosion models used to study the Chinese Loess Plateau

Abstract: The Loess Plateau suffers from severe soil erosion that leads to a series of ecological and economic problems such as reduced land productivity, exacerbated rural poverty, decreased biodiversity and sedimentation of the riverbed in the lower reaches of the Yellow River. Soil erosion models are commonly used on the Loess Plateau to help target sustainable land management strategies to control soil erosion.In this study, we compared eleven soil erosion models that were previously used on the Loess Plateau. We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 144 publications
(68 citation statements)
references
References 98 publications
1
56
0
4
Order By: Relevance
“…Another approach to erosion mapping is the use of process‐based models, such as the Pan‐European Soil Erosion Risk Assessment (PESERA) model (Irvine & Kosmas, ; Kirkby, Irvine, Jones, & Govers, ). Albeit neither the USLE nor PESERA model was included in their study, Li et al () found no clear advantage of process‐based and empirical modes over one another, after the comparison of 11 different soil erosion models.…”
Section: Introductionmentioning
confidence: 88%
“…Another approach to erosion mapping is the use of process‐based models, such as the Pan‐European Soil Erosion Risk Assessment (PESERA) model (Irvine & Kosmas, ; Kirkby, Irvine, Jones, & Govers, ). Albeit neither the USLE nor PESERA model was included in their study, Li et al () found no clear advantage of process‐based and empirical modes over one another, after the comparison of 11 different soil erosion models.…”
Section: Introductionmentioning
confidence: 88%
“…The dominance of anthropogenic activities may be a result of (a) increased demand for water resources in the Yellow River due to national economic development (Liu & Zhang, ), (b) soil and water conservation programs and eco‐environment rehabilitation campaign on the Loess Plateau (Gao et al, ; Mu et al, ), (c) the construction of water control projects (e.g., reservoirs) (Tian, Cui, Xu, & Zhou, ; G. Wang, Wu, & Wang, ). In addition, there have been a large scale of soil and water conservation measures (e.g., check dams, terraces) on the Loess Plateau since the 1970s (P. F. Li, Mu, Holden et al, ; Zhao, Mu, Wen, Wang, & Gao, ). Such measures were more influential on soil erosion than run‐off given that they were mainly designed to reduce the severe soil erosion on the plateau, leading to a more rapid reduction of sediment discharge and eventually an earlier change point in the slope of streamflow DMC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the implementation of SWAT model requires a large amount of data on topography, climate, soil, and land use (Neitsch, Arnold, Kiniry, Williams, & King, ). In many places, some of these data are not available, or the accuracy of the data is limited (P. H. Li, Mu, Holden et al, ). As a result, it is difficult to apply the SWAT model to these places or modelling results may be subject to unacceptable uncertainties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of a conceptual soil erosion model is the Morgan-Morgan-Finney (MMF) model (Morgan et al, 1984) including its revised (RMMF; Morgan, 2001) and modified (MMMF; Morgan and Duzant, 2008) versions. It has been applied in a variety of climate regions, land-use types and scales (De Jong et al, 1999;Vigiak et al, 2005;López-Vicente et al, 2008;Vieira et al, 2014;Li et al, 2017). This model retains the simplicity of empirical models yet has a stronger physical base.…”
Section: Introductionmentioning
confidence: 99%